PERFORMANCE EVALUATION OF ISLAMIC ARTIFICIAL INTELLIGENCE IN THE MUSLIM PRO APPLICATION: A SYSTEMATIC REVIEW - Iqbal, Muhammad; Ali, Muhammad; Riansyah, Fahmi Al (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This research aims to examine the performance of Islamic AI in the Muslim Pro Application in providing accurate answers related to Islamic teachings. This literature study analyzes various previous studies that evaluated the ability of the Muslim Pro Application to deliver correct and reliable information to users. The main focus of this research is to assess the accuracy of answers provided by the Islamic AI of the Muslim Pro Application and compare them with traditional sources of religious knowledge, such as Islamic scholars and texts. Findings indicate that the Islamic AI of the Muslim Pro application is capable of providing sufficiently accurate answers to basic questions about Islam. However, there are shortcomings in handling more complex questions, which require further verification from more authoritative sources. The study also found that most users are satisfied with the accuracy of the answers provided, but there is a need for further improvement, especially in terms of the depth and detail of the answers. This research recommends further development of AI algorithms and collaboration with Islamic scholars to improve the quality of answers provided by the Islamic AI of the Muslim Pro Application.